2021
DOI: 10.1155/2021/5549423
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and PSG Characteristics of Children with Mild OSA and Respiratory Events Terminated Predominantly with Arousal

Abstract: Objective. To analyze the clinical and polysomnographic characteristics in children with mild OSA and respiratory events terminated predominantly with arousal. Methods. Children aged 3–10 yrs who had mild obstructive sleep apnea (OSA) were enrolled. All children underwent polysomnography, and patients’ data were collected by using sleep-related breathing disorders (SRBD) questionnaire and OSA-18 quality of life questionnaire. Results. In total, five hundred and seventy-seven children were eligible. Children in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
2
0
1
Order By: Relevance
“…De acuerdo con la bibliografía, de los niños amigdalectomizados, hasta casi un 70% son por SAOS [ 30 ]. En nuestra muestra, el 73,7% de los niños con SAOS tenía hipertrofia amigdalar, porcentaje similar al encontrado en el estudio de Wu et al (2021) [ 30 , 47 ]. Nieminen et al (2000) encontraron que el 78% de los niños con SAOS y ronquidos y el 93% con SAOS sin ronquidos tenían hipertrofia amigdalar de grados 3 y 4 [ 28 , 30 , 46 ].…”
Section: Discussionunclassified
“…De acuerdo con la bibliografía, de los niños amigdalectomizados, hasta casi un 70% son por SAOS [ 30 ]. En nuestra muestra, el 73,7% de los niños con SAOS tenía hipertrofia amigdalar, porcentaje similar al encontrado en el estudio de Wu et al (2021) [ 30 , 47 ]. Nieminen et al (2000) encontraron que el 78% de los niños con SAOS y ronquidos y el 93% con SAOS sin ronquidos tenían hipertrofia amigdalar de grados 3 y 4 [ 28 , 30 , 46 ].…”
Section: Discussionunclassified
“…46 Sleep parameters such as arousal index and oxygen desaturation index in relation to AHI were reported in various studies. 22,24,47,48 It was reported that men are more likely to have OSA than women of nearly all ages and both sexes were more likely to have OSA patients with an AHI ≥5 increased with age, 49 and the male patients had significantly higher mean AHI than the female patients. A significant correlation was observed between the sleep parameters such as AI and ODI with age and BMI in predicting OSA.…”
Section: Ta B L E 4 (Continued)mentioning
confidence: 99%
“…and Chervin et al22 discovered that children with OSA had higher proportions of N1 sleep and lower proportions of N2 sleep compared to a control group. In a population of children with mild OSA, Wu et al23 found a greater percentage of N1 sleep and a decreased fraction of N3 sleep in an arousal predominant group. And lastly, Durdik et al 13 reported a greater percentage of N1 sleep, a lower percentage of N3 sleep and a reduced sleep efficiency in children with OSA.…”
mentioning
confidence: 98%